Cobicistat: A New Boost for the Treatment of Human Immunodeficiency Virus Infection. Issue 10 (7th March 2013) - Shah, Bhavik M.; Schafer, Jason J.; Priano, James; Squires, Kathleen E.
Abstract : Ritonavir is commonly used as a pharmacokinetic booster for antiretroviral regimens in the management of human immunodeficiency virus infections. Limitations to ritonavir boosting include increased pill burden, adverse effects, and a wide range of clinically significant drug‐drug interactions. Cobicistat is a new pharmacokinetic booster that is a selective inhibitor of cytochrome P450 3A, the main metabolizing pathway of several antiretrovirals. Cobicistat has been studied as a booster for elvitegravir, a second‐generation integrase inhibitor, and protease inhibitors. Based on successful clinical trials, a new single‐tablet regimen of elvitegravir, cobicistat, emtricitabine, and tenofovir has been approved for the management of treatment‐naïve patients. Additional studies are underway investigating the safety and efficacy of cobicistat‐boosted protease inhibitor regimens for both treatment‐naïve and treatment‐experienced patients. Cobicistat is well tolerated and may become a preferred booster for antiretroviral regimens, as it can be coformulated with several agents to create simpler regimens.